SIKAP DAN DUKUNGAN KELUARGA TENTANG PENDEWASAAN USIA PERKAWINAN PADA CALON PENGANTIN DENGAN KEHAMILAN TIDAK DIINGINKAN - M.Taufik; Rochmawati (JURNAL BORNEO AKCAYA, 2015)
Nowadays, reproductive health behavior among adolescents are considered less likely to support the realization of qualifiable youth. The decreased quality of adolescent life adversely affect the quality of the family both at present and in the future. The data of cross-sectoral collaborative program between Marriage Registry Office and Public Health Center in 2011 at work area of Sungai Kakap shows that 26 out of 178 brides were tested positive for pregnancy. Unfortunately, 18 of these brides were still at the age of adolescents. Meanwhile, in 2012, 27 out of 153 brides were also tested positive for pregnancy before got married. More unfortunately, 25 of 27 brides were also still at the age of adolescents. Therefore, this study is aimed at discovering the correlation of attitude, family support towards the maturation age of marriage, and unwanted pregnancy at work area of Puskesmas Sungai Kakap Kabupaten Kubu Raya of 2013. An observational analytic design and cross sectional approach were carried out in this study. Then, the data was statistically tested by using chi square test. Number of samples in this study were 88 brides at work area of Sungai Kakap. The results showed an attitude (p value = 0,019) and family support (p value = 0,024). Concluded that there is correlation of attitude family support towards the maturation age of marriage, and unwanted pregnancy